The automotive body volume I: components design - Morello, Lorenzo (Mechanical engineering series, 2011)
The Automotive Body consists of two volumes. The first volume produces the needful cultural background on the body; it describes the body and its components in use on most kinds of cars and industrial vehicles: the quantity of drawings that are presented allows the reader to familiarize with the design features and to understand functions, design motivations and fabrication feasibility, in view of the existing production processes. The second volume addresses the body system engineer and has the objective to lead him to the specification definition used to finalize detail design and production by the car manufacturer or the supply chain. The processing of these specifications, made by mathematical models of different complexity, starts always from the presentations of the needs of the customer using the vehicle and from the large number of rules imposed by laws and customs. The two volumes are completed by references, list of symbols adopted and subjects index. These two books about the vehicle body may be added to those about the chassis and are part of a series sponsored by ATA (the Italian automotive engineers association) on the subject of automotive engineering; they follow the first book, published in 2005 in Italian only, about automotive transmission. They cover automotive engineering from every aspect and are the result of a five-year collaboration between the Polytechnical University of Turin and the University of Naples on automotive engineering.